181k views
4 votes
Systems of equations by elimination

Systems of equations by elimination-example-1
User Plaureano
by
5.6k points

1 Answer

3 votes

Answer:

(x, y) = (2, 1)

Explanation:

given the 2 equations

2y - 3x = - 4 → (1)

6y + x = 8 → (2)

multiplying (2) by 3 allows the x terms to be eliminated

18y + 3x = 24 → (3)

add (1) and (3) term by term

(2y + 18y) + (- 3x + 3x) = (-4 + 24)

20y + 0 = 20 ( divide both sides by 20 )

y = 1

substitute y = 1 into either of the equations and solve for x

using (2), then

6 + x = 8 ( subtract 6 from both sides )

x = 2

solution (2, 1)


User Alan Tingey
by
6.3k points